Compressibility Behavior of Soft Clay Treated by Combination between Sodium Silicate and Biomass Silica Probase Stabilizer - Salim, Salman; Mat Nor, Ahmad Hakimi; Mohd Noh, Nursyazwiy Wafiy; Nor Faizal, Irfan Fauzan Ahmad; Mohd Azlan @ Atan, Muhamad Arshad Aidid (Multidisciplinary Applied Research and Innovation, 2024)
A chemically altered technique called soil stabilisation with additives can be utilised to strengthen soils with poor engineering qualities. The treatment of problematic soils, non-traditional additions such ionic, enzymes, salts, polymers, and tree resins are frequently employed. Two types of non-traditional stabilizers a powder stabiliser (biomass silica) and a liquid stabiliser (sodium silicate) based on sodium silicate were mixed with soft soil to determine the stabilisation mechanism and performance. The engineering qualities of the stabilised soil were evaluated using a macro-structural research that included consolidation, direct shear, and consolidation tests, unconfined compression strength tests, and compaction tests. A number of physical model tests were also used to assess the performance of treated laterite backfills stabilised with the chosen additives. The laboratory tests showed that the addition of 9 % as the optimum amount of both additives increased more than 80% of compressive strength after 7 and 28 days of curing periods while the consolidation settlement had been effectively reduced. The micro-structural analysis showed that the stabilisation process changed the laterite soil's porosity network. The newly created substances, known as sodium aluminosilicate hydrate gel-like product for samples treated with sodium silicate and calcium aluminate hydrate cementitious material for samples treated with biomass silica, had filled the pores of the soil. Hence, the stabilization mechanism of two selected non-traditional additives was by cationic exchange and physical bonding. The results of the physical model tests revealed that, after just seven days of curing, the stabilised backfill soil's ultimate bearing capacity improved significantly and its settling decreased in comparison to untreated backfill soft soil.